Identification of disease-linked hyperactivating mutations in UBE3A through large-scale functional variant analysis - Kellan P. Weston (Nature Portfolio, 2021)
UBE3A gene dysregulation is associated with neurodevelopmental disorders, but predicting the function of UBE3A variants remains difficult. The authors use a high-throughput assay to categorize variants by functional activity, and show that UBE3A hyperactivity increases the risk of neurodevelopmental disease.